1982
DOI: 10.1007/bf00896501
|View full text |Cite
|
Sign up to set email alerts
|

Stress management training for women on public assistance

Abstract: A life-coping skills training package for women supported by public assistance was designed to enhance self-esteem and teach life planning and stress management strategies. Ten weeks of training resulted in significant changes in scores on measures reflective of psychological distress, depression, anxiety, inadequacy, self-confidence, and ego strength. A rationale for the impact of the training is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…This research either has involved person-centred interventions, primarily focused on modifying coping strategies and teaching stress management techniques, and/or system-level interventions that attempt to reduce or remove stressors at their source, promote higher levels of social support from supervisors and co-workers, and/or change the individual's role in the setting. Positive results of coping-skills interventions in reducing psychological symptoms have been reported for women and men from various occupational groups (Harig, Price, Oleshansky, Fava, & Littman, 1992;Kline & Snow, 1994;Raymer, Sime, & Setterlind, 1992;Snow & Kline, 1995;Snow et al, 2002;Tableman, Marciniak, Johnson, & Rogers, 1982). Similarly, a number of studies targeting organizational stressors have demonstrated reductions in psychological symptoms (Heaney, Price, & Rafferty, 1992;Jackson, 1983;Wall & Clegg, 1981).…”
Section: Implications For Future Research and Workplace Interventionsmentioning
confidence: 83%
“…This research either has involved person-centred interventions, primarily focused on modifying coping strategies and teaching stress management techniques, and/or system-level interventions that attempt to reduce or remove stressors at their source, promote higher levels of social support from supervisors and co-workers, and/or change the individual's role in the setting. Positive results of coping-skills interventions in reducing psychological symptoms have been reported for women and men from various occupational groups (Harig, Price, Oleshansky, Fava, & Littman, 1992;Kline & Snow, 1994;Raymer, Sime, & Setterlind, 1992;Snow & Kline, 1995;Snow et al, 2002;Tableman, Marciniak, Johnson, & Rogers, 1982). Similarly, a number of studies targeting organizational stressors have demonstrated reductions in psychological symptoms (Heaney, Price, & Rafferty, 1992;Jackson, 1983;Wall & Clegg, 1981).…”
Section: Implications For Future Research and Workplace Interventionsmentioning
confidence: 83%
“…Once again, no follow-up measurement was undertaken. Tableman et al (1982) administered an eclectic group intervention to women receiving ®nancial aid. Improvements in symptomatology were found which were not evident in the control group.…”
Section: Qualitative Systematic Review 203mentioning
confidence: 99%
“…The impact of public assistance on the self-esteem of its recipients has been found in other studies, even in a sample of older recipients (Krause, 1996), who reported experiencing a decline in feelings of self-worth. In a study of a sample of women receiving public assistance, Tableman et al (1982) found that providing their participants with self-esteem skills and teaching them stress management and life-planning strategies had a significant impact on participants' overall mental health, specifically in the areas of depression, anxiety, self-confidence, inadequacy and ego strength.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have investigated the effectiveness of these programs and their overall impact on recipients. Research that has examined the experiences of recipients of public assistance have focused on various factors, such as self-esteem (Krause, 1996), stress (Tableman, Marciniak, Johnson, and Rodgers, 1982), marriage (Rank, 1987), duration in system (Sandefur & Cook, 1998;Strother, 1995), perception of job opportunities (Hagen & Davis, 1995a); stigma (Hagen & Davis, 1995b), and impact of work-welfare programs on children and families (Wilson, Ellwood, & Brooks-Gunn, 1995).…”
mentioning
confidence: 99%